Response of baru (Dipteryx alata Vog.) seedlings to liming and NPK application. (28th May 2017) - Zuffo, Alan Mario; Júnior, Joacir Mario Zuffo; Carvalho, Rezânio Martins; dos Santos, Adaniel Sousa; Oliveira, João Batista da Silva; Fonseca, Wéverson Lima
ABSTRACT: The definition of nitrogen doses for baru species becomes necessary because each forest species responds differently to nitrogen fertilization. The aim of this study was to evaluate baru seedlings' response to nitrogen, phosphorus, and potassium (NPK) fertilization and liming. The experiment was conducted in a greenhouse in a randomized blocks design, arranged in a 5 × 2 factorial scheme, being the factors consisted of five doses of nitrogen in covering (0, 75, 150, 225, and 300 mg dm −3 ) and substrate with and without limestone and PK, with four replications. At 60 days after transplanting, the plant height, stem diameter, number of leaflets, leaf area, shoot dry mass, chlorophyll content, N content in the leaves, root length, root volume, root dry mass, height/stem diameter ratio, shoot dry mass/root dry mass ratio, and Dickson quality index were evaluated. The substrate with liming influences positively the root dry mass. Nitrogen and PK fertilization promote increase in the relative chlorophyll content and N concentration in the leaves.